A Scoping Review: Accuracy in Early Detection of Breast Cancer Using a Clinical Breast Examination Method - Silvia Rizki Syah Putri; Rozmita Nuzula (The Indonesian Institute of Science and Technology Research, 2022)
Both globally and in Indonesia, cancer continues to be a serious health issue. The early detection program for breast cancer with the clinical breast examination method is one of the indicators of the success of health development contained in the RPJMN. According to WHO data, the incidence of cancer increased from 12.7 to 14.1 million in 2013, and the specific cause of breast cancer is still unknown. The aim of this study is to review the clinical breast examination method's accuracy for early breast cancer detection is the goal. The method is using the a scoping review method covering Population, Exposure, Outcome, Study Design (PEOS). It approach is to construct a review topic and search strategy. Eight papers from three databases were analyzed (Pubmed, Science Direct, and EBSCO). Articles chosen using Prism Flowcharts and Hawker's Critical Appraisal. Results shows that the eights publications analyzed, five articles used a cohort research design, two articles used an RCT study design, and one article used a cross-sectional study design. The clinical breast examination (CBE) approach is for early diagnosis of breast cancer has low accuracy. It is due to the influence of CBE implementation skills. However, when used in tandem with mammography, CBE can produce more sensitive results. The CBE method is seen as less complicated and more affordable, making it one of the suggested early detection techniques for breast cancer in developing nations.